2022
DOI: 10.1039/d2nr02765h
|View full text |Cite
|
Sign up to set email alerts
|

Single-ion chelation strategy for synthesis of monodisperse Pd nanoparticles anchored in MOF-808 for highly efficient hydrogenation and cascade reactions

Abstract: Ultrafine Pd nanoparticles are prepared using a single-ion precursor on the carrier MOF-808. The ligand 2,3-pyrazinedicarboxylic acid (Pza) is dispersed in porous MOF-808 via grafting on formic acid sites, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Nowadays, most halogenated arylamines are obtained from the corresponding halogenated nitroarenes through reduction. The main reduction methods in the industry include iron powder reduction, alkali sulphide reduction, electrolytic reduction, hydrogen transfer reduction, catalytic hydrogenation reduction, and so on. Among them, catalytic hydrogenation reduction has a wide foreground due to the advantages of environmental benignancy, high efficiency, low cost, and low energy consumption. …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most halogenated arylamines are obtained from the corresponding halogenated nitroarenes through reduction. The main reduction methods in the industry include iron powder reduction, alkali sulphide reduction, electrolytic reduction, hydrogen transfer reduction, catalytic hydrogenation reduction, and so on. Among them, catalytic hydrogenation reduction has a wide foreground due to the advantages of environmental benignancy, high efficiency, low cost, and low energy consumption. …”
Section: Introductionmentioning
confidence: 99%
“…34,[47][48][49][50] As a result, to design and produce an effective catalyst, the selection of an appropriate biopolymeric support, which has various merits including ecologically benign nature, the use of harmless metals, and reproducibility, is the focal point of GC in the 21st century. [51][52][53][54] In recent decades, natural polymers have received extensive consideration as outstanding supports for sustainable chemistry 23,46,[55][56][57][58][59] since they possess both free amine and OH functional groups simultaneously and are capable of reacting with both nucleophiles and electrophiles through ion pairs and hydrogen bonding. 53,60 Commonly, biopolymers have no destructive impact on the environment as they are biodegradable and obtained from renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…27 Based on these strategies, active metal sites can be inherently embellished at the pore surfaces with the host frameworks, which will greatly improve the free diffusion of reactant molecules, thus realizing highly efficient catalysis. 34 As early as in 1994, a layered MOF of the [Cd (bpy) 2 (NO 3 ) 2 ]•guest (bpy = 4,4′-bipyridine) was prepared by Fujita et al 35 For the first time, they demonstrated the utility of this MOF as a Lewis acid catalyst, which boosted the cyanosilylation of aldehydes with shape selectivity. Unfortunately, in most cases of MOF structures, any changes of the metal ions in the secondary building unit must ensure the integrity of the network, and the coordination spheres of metal nodes are easily occupied by organic ligands.…”
Section: Introductionmentioning
confidence: 99%